PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI TERHADAP USAHA JARING IKAN DI DESA ERIS, KECAMATAN ERIS, KABUPATEN MINAHASA - Imanuel K. Ch. Walingkas; Gene H. M. Kapantow; Eyverson ., Ruauw (Sam Ratulangi University, 2016)
The objective of this research is to study the use of information and communication technology on fish net enterprise at Eris Village Minahasa Regency. This research is conducted for three months from July, 2015 to September, 2015. This research uses census method with primary data taken directly by using questionnaire to interview 47 fisherman and secondary data regarding socioeconomic condition taken from government institution: Eris Village Office and Eris sub-district Office. The research result showed that only 55,32 percent of fisherman at Eris Village that use information and technology especially internet. The majority fisherman farmers are accessing internet via hand phone, smartphone, and tablet. The majority of fishermen using internet 80,77 percent have used to look for information related with fishing net business. The most dominant use of internet is for tool in buying product/need for fish net enterprise, followed by looking for information about the way/technique of fish net culture. The major constraint in using of internet at Eris Village is the still not good of internet connection (signal) and the low of farmer ability in accessing internet.